1998
DOI: 10.1177/002199839803200805
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of Clearance and Interference Fits in a Pin-Loaded Cross-Ply FGRP Laminate

Abstract: The elastic behavior of a cross-ply fiber glass-reinforced epoxy laminate loaded in tension through a pin fitted with clearance and interference is examined. A nonlinear contact analysis using the Finite Element Method and an experimental study by Speckle Interferometry are performed, showing fairly good correlation. An interesting comparison is performed between FEM results and Hertzian contact theory. Major conclusions are: (I) clearance causes high compressive stress in the bearing area, and does not influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 10 publications
3
30
0
Order By: Relevance
“…This may be also due to fiber reinforcement at 0°and 90°direction. According to the results of the previous studies [5,13], the stress magnitude was consistent regardless of the directions. This study presented stresses in both radial and tangential directions can vary depending on the angles around the hole.…”
Section: Fe Simulation Of the Pin Installation Processsupporting
confidence: 70%
See 4 more Smart Citations
“…This may be also due to fiber reinforcement at 0°and 90°direction. According to the results of the previous studies [5,13], the stress magnitude was consistent regardless of the directions. This study presented stresses in both radial and tangential directions can vary depending on the angles around the hole.…”
Section: Fe Simulation Of the Pin Installation Processsupporting
confidence: 70%
“…Fatigue enhancement by interference-fit may be due to local pre-compression stresses induced by interference-fit, which improves the joint stiffness. It was also found that interference-fit decreases the degradation rate of joint stiffness per unit bearing area over the fatigue cycles, resulting in delaying damage progression [5,6].…”
Section: Fatigue Enhancement Of Interference-fit Pin Loaded Gfrpmentioning
confidence: 97%
See 3 more Smart Citations